Seroprevalence of Rickettsia bellii and Rickettsia felis in dogs, São José dos Pinhais, State of Paraná, Brazil - Fernanda Silva Fortes (Revista Brasileira de Parasitologia Veterinária, 2010)
Brazilian spotted fever (BSF) is a vector-borne zoonosis caused by Rickettsia rickettsii bacteria. Dogs can be host sentinels for this bacterium. The aim of the study was to determine the presence of antibodies against Rickettsia spp. in dogs from the city of São José dos Pinhais, State of Paraná, Southern Brazil, where a human case of BSF was first reported in the state. Between February 2006 and July 2007, serum samples from 364 dogs were collected and tested at 1:64 dilutions by indirect immunofluorescence assay (IFA) against R. rickettsii and R. parkeri. All sera that reacted at least to one of Rickettsia species were tested against the six main Rickettsia species identified in Brazil: R. rickettsii, R. parkeri, R. bellii, R. rhipicephali, R. amblyommii and R. felis. Sixteen samples (4.4%) reacted to at least one Rickettsia species. Among positive animals, two dogs (15.5%) showed suggestive titers for R. bellii exposure. One sample had a homologous reaction to R. felis, a confirmed human pathogen. Although Rickettsia spp. circulation in dogs in the area studied may be considered at low prevalence, suggesting low risk of human infection, the present data demonstrate for the first time the exposure of dogs to R. bellii and R. felis in Southern Brazil.